Effectiveness of Beta Blockers against Hypertrophic Cardiomyopathy - Bhatti, Hammad-Ur-Rehman; Jahan, Naseem; Ahmed Shah, Zahoor (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate the effectiveness of beta blockers against hypertrophic cardiomyopathy. Study design: Retrospective study Place and duration of study: Department of Medicine, Islam Medical College, Sialkot from 01-10-2020 30-01-09-2021. Methodology: One hundred and thirty six confirmed hypertrophic cardiomyopathy cases within the age of 3-75 years were enrolled. Different types of beta blocker used and its efficacy result and side effects were documented. The average efficacy was assessed for each beta blocker uptil 5 years’ survival rate. Results: High doses of beta blocker were indicated for hypertrophic cardiomyopathy patients in majority of the cases. The efficacy of various beta blockers shows that cardio-selective blocker is much better in efficacy. Left ventricle outflow tract (LVOT) with a value greater or equal to 50 mmHg was observed in patients at or greater than 70 years. Conclusion: Beta blockers are effective in hypertrophy cardiomyopathy cases depending upon the left ventricle out flow tract for better outcome.